Habermas, post-metaphysical thinking, and the problem of Muslim minorities in Europe - Byrd, Dustin (Ciências da religião história e sociedade, 2014)
The Critical Theorist Jürgan Habermas has increasingly become more con-cerned about the issue of religion in Europe, especially the difficulties that new Islamic immigrants are having integrating and assimilating into secular European society. Habermas proposes that religious voices, especially those of Muslims, not be ex-communicated from the public discourse but rather be welcomed in. However, in order to do this, he requests that the ideals, principles, and values of Islam go through a “translation” process, that they be rendered into publicly accessible (secular) language so that the non-reli-gious community can enter into a discourse with religious voice via a shared common language. Additionally, the secular voices of European society have also to go through a learning process; they have to cultivate a sensitivity to-wards religious beliefs, understanding them to be invaluable for the demo-cratic processes due to the fact that their views can be meaningful sources of moral analysis and motivation for solidarity which has been depleted by secular modernity. This process is not without its problems as a discourse between the secular and the religious have been continually pulled apart via anti-Islamic actions as well as anti-Western terrorism. This situation has left the Muslim community isolated, self-ghettoized, and a virtual nation of stateless people within Europe, which has made reactionary Islamic funda-mentalism more attractive to young Muslims alienated from European so-ciety. It is the purpose of this paper to highlight the major difficulties that Habermas’ project of reconciliation will encounter and offer a critical prog-nosis of what to expect should this project materialize.